2009
DOI: 10.1210/en.2008-1016
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-Dependent and -Independent Estrogen Receptor-α Signaling Separately Regulate Male Fertility

Abstract: Estrogen receptor-alpha (ERalpha) plays a critical role in male reproductive tract development and fertility. To determine whether estrogen-dependent and -independent ERalpha mechanisms are involved in male fertility, we examined male estrogen nonresponsive ERalpha knock-in mice. These animals have a point mutation (G525L) in the ligand-binding domain of ERalpha that significantly reduces interaction with, and response to, endogenous estrogens but does not affect growth factor activation of ligand-independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…49 Study using estrogen non-responsive ESR1 knock-in (ENERK1) mice, which have a point mutation in the ligand-binding domain of ESR1 that significantly reduces interaction with endogenous estrogens, without affecting ligand-independent ESR1 pathways mediated by growth factors, confirmed that estrogen-dependent ESR1 signaling is required for germ cell viability, most likely through support of Sertoli cell function. 60 The GPER (mRNA and protein) is present in rat Sertoli cells as reported by our laboratory. 49 GPER immunostaining was Figure 1.…”
Section: β-Estradiol Signaling and Regulation Of Sertoli Cellsmentioning
confidence: 64%
“…49 Study using estrogen non-responsive ESR1 knock-in (ENERK1) mice, which have a point mutation in the ligand-binding domain of ESR1 that significantly reduces interaction with endogenous estrogens, without affecting ligand-independent ESR1 pathways mediated by growth factors, confirmed that estrogen-dependent ESR1 signaling is required for germ cell viability, most likely through support of Sertoli cell function. 60 The GPER (mRNA and protein) is present in rat Sertoli cells as reported by our laboratory. 49 GPER immunostaining was Figure 1.…”
Section: β-Estradiol Signaling and Regulation Of Sertoli Cellsmentioning
confidence: 64%
“…The effects of estrogen are mediated by at least 2 ER subtypes (ERα and ERβ), and these subtypes are expressed in various stages of human germ cells (Couse and Korach, 1999;Carreau et al, 2006). An important role for estrogen in male reproduction has been suggested by both animal models and the phenotypes of men with ERα and ERβ gene mutations (Krege et al, 1998;O'Donnell et al, 2001;Gould et al, 2007;Sinkevicius et al, 2009). Consequently, ERα and ERβ have become candidate spermatogenesis genes in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The ES signaling is known to be mediated by at least two functional isoforms of estrogen receptors (ER) known as ERα and ERβ that are encoded by two different genes on the long arm of chromosomes six (6q25) and 14 (14q23-24), respectively [22]. In human testis, ERα and ERβ were also found in ejaculated spermatozoa, early meiotic spermatocytes and elongated spermatids-independent ERα signaling is important for concentrating epididymal sperm, whereas estrogen-mediated ERβ signaling is essential for germ cell progression or viability [96]. The ER genes thereby represent a logical target for mutational analysis in the infertile male.…”
Section: The Estrogen Receptors (Esr) Genes Mutationsmentioning
confidence: 99%